Odontogenic tumors: A retrospective study of four Brazilian diagnostic pathology centers - da-Costa, Daniela O P. (Medicina Oral S.L., 2012)
Objective: This article presents the results of a retrospective study of the frequency and classification of odontogenic tumors recorded at four centers of diagnostic pathology in Rio de Janeiro, Brazil. Study Design: All medical records and microscopic slides of odontogenic tumor specimens for the years 1997 to 2007 were retrieved from the files of four services of diagnostic pathology in Rio de Janeiro City. Diagnoses were re-evaluated and the tumors classified according to the latest (2005) World Health Organization Classification of Tumors. Results: A total of 201 odontogenic tumors were found among 15,758 oral biopsies (1.3%). The frequencies of these tumors at the four centers ranged from 0.5% at the National Cancer Institute to 3.3% in a private laboratory. Chi-square analysis revealed statistically significant differences (p<0.05) between the proportions of odontogenic tumors in the studied centers. Of these, 94.5% were benign and 5.5% were malignant. Keratocystic odontogenic tumor (32.3%) was the most frequent lesion, followed by ameloblastoma (29.8%) and odontoma (18.4%). Conclusions: Odontogenic tumors are uncommon in Brazil. Different pathology laboratories reported divergent frequencies of odontogenic tumors, which may reflect institutional specializations and the patient populations served. Key words:Odontogenic tumors, jaw neoplasms, epidemiology, WHO classification.